The Effect of Task Base Language Teaching (TBLT) on Tertiary ESOL Learners’ Academic Writing Achievement - I Wy Dirgeyasa (Journal of Education and Learning (EduLearn), 2018)
The aim of the study was to investigate the effect of Task Base Language Teaching (TBLT) on tertiary ESOL learners’ academic writing achievement in tertiary level. Therefore, the experimental research was applied to this study. The control group was taught through Classical Method (CM) while the experiment group was taught through Task Based Language Teaching (TBLT) method. Furthermore, the pre-test and post-test were administered to students in control group and experiment group (30 students in each group). The data were tabulated by employing t-test in Statistical Package for Social Science (SPSS) version 21. Based on the data analysis, the result indicated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that there was a significant effect of Task Based Language Teaching (TBLT) method on tertiary ESOL learners’ writing achievement compared to Classical Method (CM) of teaching.